Group Acceptance Sampling Plans for Resubmitted Lots UnderType II Generalized Half Logistic Distribution - Rao, G. S.; Jilani, S.; Rao, A. V. (Journal of Scientific Research, 2020)
In this research article, we build-up a group acceptance sampling plan (GASP) for a resubmitting lot when the lifetime of a product follow the Type II Generalized half-logistic distribution (GHLD). The design parameters of the group acceptance sampling plan for the resubmitted are determined by fixing the experiment termination time and the numbers of testers at the stated producer’s and consumer’s risks both satisfy at the same time. We contrast the proposed GASP with the ordinary group sampling plan and the results are demonstrated with a live data set.